Investigating impacts of climate change and responses of botanical gardens in Gauteng province - Mosia, Malehloa (Vaal University of Technology, 2022)
Worldwide, botanical gardens are used as critical recreational centres for urban tourism, where people can relax and learn about flora. Botanical gardens have a crucial role to play in conservation and tourism and have an essential role in conserving and maintaining plants and animal species. However, there is growing concern that botanical gardens and other protected areas could be at risk from climate variability and change. Regardless of this concern, very little on how climate variability and change will affect botanical gardens worldwide is known. This study sought to respond to this knowledge gap identified and aimed to examine the evidence, impact, and response to climate variability and change by the Pretoria National botanical gardens and Walter Sisulu botanical gardens in Gauteng province. The study adopted a pragmatism paradigm, with a case study that used a mixed-method approach. The study used multiple research techniques to collect data, such as; an online survey (324), key informants interviews (15), field observations and secondary data analysis. Data was analysed using a Mann-Kendall Trend Analysis, Microsoft excel sheet and Question-Pro analysis tools. Content and thematic analysis were used to analyse secondary and interview data. The study found evidence of climate variability and change at the two botanical gardens, characterised by intense rainfall activity such as flooding, extreme droughts, generally decline in rainfall amounts, and increasing temperature, posing a threat to infrastructure, flora, and fauna of the garden. Recreation makers complained that climate change adversely affects botanical gardens' aesthetics and general experience. In response to climate variability and change, botanical gardens in Gauteng are trying to adapt and mitigate the effects of climate change to foster climate resilience. As much as there are fears of climate variability and change impacts, botanical gardens are underprepared to deal with climate change, given the vast knowledge gaps that exist. This study recommends that scientific studies be conducted to ascertain how climate variability affects flora and fauna in the botanical gardens as there are many grey areas. Hopefully, this will prompt the gardens to adapt to climate variability and change effects appropriately.
MM (TTSM) (Department of Travel and Tourism Services Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Climate change impact; Variability; Botanical gardens; Gauteng province; Tourists; South Africa; Dissertations, Academic -- South Africa.; Climatic changes -- South Africa.; Botanical gardens -- South Africa.; Tourism -- South Africa -- Gauteng.